2018
DOI: 10.1093/cercor/bhy163
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Posterior Parietal Cortex Contribution to Spatial but not Temporal Numerosity Perception

Abstract: Posterior parietal cortex (PPC) is thought to encode and represent the number of objects in a visual scene (i.e., numerosity). Whether this representation is shared for simultaneous and sequential stimuli (i.e., mode independency) is debated. We tested the existence of a common neural substrate for the encoding of these modes using fMRI. While both modes elicited overlapping BOLD response in occipital areas, only simultaneous numerosities significantly activated PPC. Unique activation for sequential numerositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 77 publications
6
26
1
Order By: Relevance
“…Congruently with previous studies using delayed comparison tasks (Cavdaroglu and Knops, 2018;Cavdaroglu et al, 2015) we observed that match trials, during which a comparison was made, elicited stronger signals in intraparietal areas with respect to sample trials. Once again, our analysis methods allowed us to more precisely pin down the location of these activations within the IPS than done previously, and compare it to the ones observed during mere perception.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Congruently with previous studies using delayed comparison tasks (Cavdaroglu and Knops, 2018;Cavdaroglu et al, 2015) we observed that match trials, during which a comparison was made, elicited stronger signals in intraparietal areas with respect to sample trials. Once again, our analysis methods allowed us to more precisely pin down the location of these activations within the IPS than done previously, and compare it to the ones observed during mere perception.…”
Section: Discussionsupporting
confidence: 88%
“…However, independent of the execution of such numerical operations, enhanced activity for numbers as opposed to letters or colors was also to a lesser extent measured in HIPS during an orthogonal target detection task (Eger et al, 2003). Moreover, parietal regions were reported to habituate to repeated presentation of the same numerical quantity and show numerical distance-dependent recovery of activity for deviant numbers Cantlon et al, 2006;Ansari et al, 2006b) to some extent even across formats (Piazza et al, 2007;Vogel et al, 2017), to encode numerical quantity in multi-voxel patterns of evoked activity (Borghesani et al, 2018;Bulthé et al, 2014;Castaldi et al, 2016Castaldi et al, , 2019Cavdaroglu and Knops, 2018;Damarla and Just, 2013;Eger et al, 2009Eger et al, , 2015Lasne et al, 2018) and to contain topographically organized numerosity maps (Harvey et al, 2013;Dumoulin, 2017a, 2017b).…”
Section: Introductionmentioning
confidence: 97%
“…It should be noted that we used temporally distributed tactile numerosity stimuli as the WM memoranda, namely the numerosity, was presented as a sequence of pulses. Evidence exists for potential differences in perceptual processing of spatially and temporally distributed numerosities, where spatially distributed stimuli appear to be processed in parietal regions while temporarily distributed stimuli do not (Cavdaroglu and Knops, 2019). In line with the finding of Cavdaroglu and Knops (2019), we used temporally distributed stimuli and did not find evidence of WM representations in posterior regions in our full brain FWE-corrected analysis.…”
Section: Discussionsupporting
confidence: 75%
“…It is important to note that in a natural context, where the dimensions are not isolated as in the current experimental paradigm and, thus, strongly correlate with each other, early stage visual discrimination would likely be much stronger. Indeed, recent neuroimaging evidence supports a numerosity representation both in parietal and occipital areas, with an increasing sensitivity to numerosity along the dorsal stream especially when the numerosity is related to a task (50,51).…”
Section: Discussionmentioning
confidence: 98%